(untitled) (Global Journal of Computer Science and Technology, 2021)
The information available to the system is incomplete in many applications particularly in Decision Support Systems The fuzzy logic deals incomplete information with belief rather than likelihood probability Sometimes the decision has to be taken with fuzzy information In this paper fuzzy machine learning is studied for decision support systems The fuzzy Decision set is defined with two-fold fuzzy set The fuzzy inference is studied with fuzzy neural network for fuzzy Decision sets Business application is given as application